A Single‐Crystalline Mesoporous Quartz Superlattice. Issue 20 (6th April 2016) - Matsuno, Takamichi; Kuroda, Yoshiyuki; Kitahara, Masaki; Shimojima, Atsushi; Wada, Hiroaki; Kuroda, Kazuyuki
Abstract: There has been significant interest in the crystallization of nanostructured silica into α‐quartz because of its physicochemical properties. We demonstrate a single‐crystalline mesoporous quartz superlattice, a silica polymorph with unprecedentedly ordered hierarchical structures on both the several tens of nanometers scale and the atomic one. The mesoporous quartz superlattice consists of periodically arranged α‐quartz nanospheres whose crystalline axes are mostly oriented in an assembly. The superlattice is prepared by thermal crystallization of amorphous silica nanospheres constituting a colloidal crystal. We found that the deposition of a strong flux of Li + only on the surface of silica nanospheres is effective for crystallization. Abstract : Order a double : A single‐crystalline mesoporous quartz superlattice with periodic order on both the several tens of nanometer scale and the atomic scale is prepared by crystallization of amorphous silica nanospheres which constitute a colloidal crystal. The periodic arrangement of silica nanospheres is retained even though Li + ions are used as a strong flux.